Analisis Keterampilan Shooting Pada Permainan Sepakbola Di Smp Negeri 39 Seluma - Saputra, Riko Gion; Febrianti, Mariska; Putra, Dwingki Marta (Jurnal Pendidikan Rafflesia, 2024)
This study aims to determine the shooting skills in football games at SMP Negeri 39 Seluma. This type of research is qualitative descriptive research. The research sample consisted of 25 people. The instrument used in this study was the Football Shooting Test. Where the results of the analysis of shooting skills in football games at SMP Negeri 39 Seluma in this study showed the classification of "good" to "very poor". Then where are the results of the final shooting skills test in football games at SMP Negeri 39 Seluma, as follows: that out of 25 football players at SMP Negeri 39 Seluma. As many as 7 people (28%) have the category of less. As many as 12 people (48%) have the category of sufficient. As many as 5 people (20%) have the category of good and as many as 1 person (4%) have the category of very good. It can be concluded based on these data that the shooting skills test in football games at SMP Negeri 39 Seluma is in the sufficient category, namely as many as 12 athletes or with a percentage of 48%.